MODEL PERANGKAT RPP BAHASA INGGRIS SATU HALAMAN UNTUK PEMBELAJARAN MASA KRISIS - Rahmad Junaidi; Fauzan Putra Albahri (IAI Al-Mawaddah Warrahmah Kolaka, 2021)
Curriculum changes for improvement are keep being pursued to get maximum results and at the end the latest policy is the teacher's should make single page lesson page (RPP). The condition and the single page lesson page (RPP) is appropriate to be chosen for model in online learning because it only consists of one page, concise and practical as well. The single page lesson plan policy has received attention from various parties, especially English teachers because it is a new thing and becomes a challenge in teaching processes. A lesson plan must contain components such as identity, learning objectives, and systematic learning activities, learning methods and media used as well as learning resources and time needed. These components are important as a guide for teachers in carrying out learning according to what has been planned. The lesson plans made by the teacher are expected to be able to accommodate students' conditions and the characteristics of the subjects and subjects raised here are English subjects. The research model used is the Plomp model (2007). This model consists of three stages, they are first stage of initial assessment (preliminary research), the second stage is the design stage (prototype phase) and the last stage is the assessment phase (assessment phase).